Biology, etiology, and control of virus diseases of banana and plantain - Kumar, P. Lava; Selvarajan, R.; Iskra Caruana, M.L.; Chabannes, M.; Hanna, R. (Elsevier, 2014)
Banana and plantain (Musa spp.), produced in 10.3 million ha in the tropics, are among the world's top 10 food crops. They are vegetatively propagated using suckers or tissue culture plants and grown almost as perennial plantations. These are prone to the accumulation of pests and pathogens, especially viruses which contribute to yield reduction and are also barriers to the international exchange of germplasm. The most economically important viruses of banana and plantain are Banana bunchy top virus (BBTV), a complex of banana streak viruses (BSVs) and Banana bract mosaic virus (BBrMV). BBTV is known to cause the most serious economic losses in the “Old World,” contributing to a yield reduction of up to 100% and responsible for a dramatic reduction in cropping area. The BSVs exist as episomal and endogenous forms are known to be worldwide in distribution. In India and the Philippines, BBrMV is known to be economically important